INTERNSHIP PROGRAM AT LKP SAFIRA ENGLISH COURSE: - Sari, Cindy Prastika; Islamiyah, Ulil (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2024)
This article on community service activities is written from the report of the students' internship for approximately three months at LKP Safira English Course Situbondo. The implementation team consisted of two students from the English Literature study program. While engaged at the partner institution, the team encountered issues related to the limited number of tutors and the lack of variety in teaching methods. Therefore, the team took the initiative to provide solutions in the form of integrating educational games into the learning process, strengthening vocabulary, creating wall magazines, and producing creative content. The activities carried out proved to have a positive impact on the students of LKP Safira English Course. They appeared more enthusiastic about learning due to the varied methods and media of instruction. From this, it can be concluded that the students' PKL activities at LKP Safira English Course can help address issues related to learning.